Low Expression of TLR-1, -2, -4 a IL-2, -2R, -10, -10R and TGFb1 in Pseudosynovial Tissue Collected at Revision Total Knee Arthroplasty for Aseptic Loosening - Tománková, T.; Kriegová, E.; Fillerová, R.; Lužná, P.; Ehrmann, J.; Gallo, J. (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
Aseptic loosening (AL) and periprosthetic osteolysis (PPOL) in total hip (THA) and knee (TKA) arthroplasty are linked to an inflammatory process initiated by wear debris released from artificial joints. There is still limited information about the contribution of Toll-like receptors (TLRs) and distinct regulatory cytokines to AL/PPOL in both joints. In this study, we investigated mRNA expression of TLR-1,-2,-4 and cytokines/receptors (IL-2,-2R,-10,-10R, TGFb1) in pseudosynovial tissue obtained from 55 patients with aseptically failed THAs/TKAs and 37 control patients with hip/knee primary osteoarthritis (OA) using quantitative RT-PCR. Immunohistochemical staining was used to detect the corresponding proteins. Non-parametric Kruskal-Wallis and Mann-Whitney tests were used to determine differences between the patient groups. When comparing expression profiles between patients with aseptically failed THA and TKA, higher amounts of TLR-1,- 2,-4 and IL-2R mRNA transcripts were detected in THA patients. The mRNA expression of studied molecules (TLR-1,-2,-4, IL-2, IL-10, IL-2R, IL-10R, TGFb1) did not differ between THA and OA hip tissues. Lower mRNA expression of TLR-1,-2,- 4, IL-10, and IL-10R was detected in TKA when compared to control knee OA. Similar mRNA profiles of IL-2, IL-2R, and TGFb1 were observed in TKA and knee OA. Using immunohistochemistry, we detected low expression of TLR-1 protein in failed THA/TKA, whereas TLR-2 protein levels were higher in TKA/THA patients than in OA controls. High individual variability in TLR-4 protein levels was detected among patients with aseptically loosened THA and TKA. IL-10 protein levels were similar in THA and TKA patient subgroups and control subjects, whereas IL-10R protein level was higher in failed TKAs and OA controls than in THAs. No difference in IL-2 protein levels was detected between patients with THA/TKA and those with OA. Our data indicate close similarity between the expression patterns in aseptically failed THA and TKA. However, certain differences were observed which also suggest unique pathways associated with the end-stage of aseptic loosening in THA and TKA. For instance, differences in the size, shape and load of polyethylene particles between THA and TKA could play some role. The composition of THA and TKA and differences in terms of mechanical forces might also be involved. This is the fist study comparing the gene expression profile of a particular set of innate immunity regulatory molecules between tissues from aseptically failed THA and TKA. Low expression of TLR-1,-2,-4 and cytokines/receptors (IL-2, IL-2R, IL-10, IL-10R, and TGFb1) was observed in pseudosynovial tissues obtained from aseptically failed THAs and TKAs. Higher amount of TLR transcripts was detected in THA as compared to TKA. These findings indicate certain differences in the mechanism of aseptic loosening occurring at the site of THA and TKA. Further research is warranted.